UBQLN4 promotes progression of HCC via activating wnt-β-catenin pathway and is regulated by miR-370 - Yan Yu; Penglin Xu; Guangying Cui; Xiaodong Xu; Kongfei Li; Xiaolong Chen; Jie Bao (Cancer Cell International, 2020)
Abstract Background Ubiquilin-4 (UBQLN4) is a member of the ubiquitin–proteasome system that is usually upregulated in many tumor cells. Its overexpression has been associated with poor disease outcomes in various cancer diseases. However, the underlying mechanism of UBQLN4 in the development of hepatocellular carcinoma (HCC) has not been elucidated. Methods Immunochemistry, real-time PCR, and western blotting were used to evaluate the expression levels of UBQLN4 in cancer tissues. Univariate, Cox-regression, and Kaplan–Meier analyses were performed to determine the association between UBQLN4 expression and HCC prognosis. Cell Counting Kit-8 (CCK-8), transwell, EDU and colony formation assays were conducted to evaluate the role of UBQLN4 in HCC cell progression. The gene set enrichment analysis and luciferase reporter experiments were conducted to find the mechanism of UBQLN4 in HCC. Results Ubiquilin-4 (UBQLN4) was overexpressed in HCC tissues. Besides, overexpression of UBQLN4 was associated with poor overall survival and disease-free survival rate of HCC patients. The loss-of-function analysis revealed that suppression of UBQLN4 inhibited the proliferation and invasion of HCC cells in vivo and in vitro. The KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis showed that UBQLN4 could regulate activation of the wnt-β-catenin pathway in HCC cells. Furthermore, our results showed that UBQLN4 was downregulated by miR-370, which acted as a tumor suppressor gene in HCC progression. Conclusion The results of the present study suggest that the miR-370/UBQLN4 axis may play a critical role in the progression of HCC. These findings may inform future strategies for the development of therapeutic agents against HCC.